Пошкоджуваність та руйнування циліндричних твелів ядерних реакторів - Бреславський, Дмитро Васильович; Сенько, Альона Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Стаття містить опис методу та алгоритмів розрахунку двовимірних задач повзучості, яка супроводжується накопиченням прихованої пошкоджуваності, та руйнування, процес якого обумовлено зародженням та поширенням макроскопічного дефекту. В основі методу розв’язання задачі є комбінація методу скінченних елементів та методу прогнозу-корекції третього по-рядку для інтегрування за часом. В розрахунках застосовується скінченноелементний комплекс FEM Creep та комп’ютерна програма FEM Creepdamagefracture, яка реалізує процес змінювання сіток та граничних умов задачі згідно з перебігом процесу руйнування. Розглянуто модель твелу ядерного реактору атомних електричних станцій, яка включає паливо та оболонку, виконано моделювання накопичення пошкоджуваності та подальшого руйнування. Чисельними розрахунками встановлено час закінчення прихованого та повного руйнування, для різних моментів часу визначено форму дефекту.

The paper contains the description of method and calculation algorithms for two-dimensional problems of creep-damage and fracture caused by development the macroscopic defect. The method of problem solution is based on combination of Finite Element and time integration third order predictor-corrector methods. The finite element software FEM creep and computer code FEM Creep damage fracture for modification of grids and boundary conditions, which are gone with fracture process behavior, are used in calculations. The resulting system of differential equations, which includes right part caused by traction and additional forces caused by creep strains, is presented. The plane triangular finite element is used in numerical analysis. The model of fuel rod cross section was re-garded. It includes uranium fuel and metal cladding. The constitutive equations for fuel were built by use of Norton and Kachanov-Rabotnov laws for cases of varying temperatures. The constants which are included in creep-damage constitutive equations for fuel were processed by use of experimental curves at different temperatures. The comparison between experimental and calculated datais presented. The fracture algorithm was built by use the idea of gridmodification due to exception of ‘failed’ elements. The calculations with modified grids and, if necessary, the boundary conditions, are continued until the moment ofachieving the critical dimensions of macroscopic defect. The numerical simulation of creep-damage process and macroscopic defect’s growth was carried out and damage distribution in fuel rod’s cross section as well its current geometry were determined by way of finite elements exclusion.
Damage and fracture of fuel rods of nuclear reactors
Keywords: повзучість; твел; метод скінченних елементів; creep; fuel rod; finite element method